Liver Biopsy in Children in Dhaka Shishu Hospital A Study of 30 Cases (Bangladesh Journal of Child Health, 2010)
Background: Liver biopsy is an established procedure to diagnose disease, to assessprognosis and to follow up of liver diseases. Although liver biopsy is a confirmatory diagnosticprocedure of majority of the hepatological disorders, it carries the risk of complications.Though major complications rarely occur, minor complications are common. To minimizecomplications, several biopsy techniques have been developed. The present study wasintended to correlate the clinical diagnoses with histological diagnoses and to observethe complications encountered by the children with percutaneous liver biopsy procedure.Patients and Methods: A total of 30 paediatric patients of suspected liver diseases,based on predefined eligibility criteria, were subjected to biopsy for confirmation ofdiagnosis. An ultrasound of liver was routinely performed before the procedure to markthe site for percutaneous biopsy. The field was prepared with alcohol-based solution(povidone-iodine) and sterile drapes were placed over the patient. Local anaestheticwas administered with 2% lidocain solution 20mg/ml (preferably levobupivacaine 2.5mg/ml) in both superficial and deep planes. A blind liver biopsy was done at the point ofmaximum dullness by percussion over the right trunk. We used cutting needle. Thediameter of the needle used in our study was 14-gauge (1.4 mm) which allowed adequatecollection of tissue for diagnosis. The biopsy material was taken in a very small amountof sterile normal saline and was immediately sent to the laboratory for evaluation.Results: Half (50%) of the patients was more than 5 years of age with median agebeing 5.0±3.9 years. Majority (80%) was male. Ninety percent of the patients belongedto poor socioeconomic class. Clinically the cases were diagnosed as having chronichepatitis (23.3%) followed by CLD (16.7%), isolated hepatomegaly (16.7%), livercirrhosis (13.3%) and storage disease (13.3%). Hepatosplenomegaly and congenitalhepatic fibrosis, each was 6.7%. Histological diagnoses of biopsy material obtainedfrom the liver confirmed that one-sixth (16.7%) of the cases had liver cirrhosis. Storagedisease and glycogen storage disease each comprised 13.3% of the cases andcongenital biliary atresia 10%. Very few cases had moderate fatty changes withcholestasis, congenital hepatic fibrosis, chronic inflammatory cells, chronic viralhepatitis and secondary biliary cirrhosis. Nearly half (46.7%) patients had mild painand discomfort at the site of biopsy, most of which spontaneously went away. However,some 3 (10%) patients developed major complications needing management.Conclusion: Liver biopsy is a well established procedure in the diagnosis and follow upof liver diseases. But it is not without risk of complications. So, before deciding for aliver biopsy, the indications and risks must be assessed cautiously for each patient.Key words: Percutaneous liver biopsy; clinical diagnoses; histological diagnoses; complications.DOI: 10.3329/bjch.v34i1.5694Bangladesh Journal of Child Health 2010; Vol.34(1): 1-6